U(2) flavor physics without U(2) symmetry - De Andrade, M. A.; Vancea, I. V. [UNESP] (Elsevier, 2000)
We present a model of fermion masses based on a minimal, non-Abelian discrete symmetry that reproduces the Yukawa matrices usually associated with U(2) theories of flavor. Mass and mixing angle relations that follow from the simple form of the quark and charged lepton Yukawa textures are therefore common to both theories. We show that the differing representation structure of our horizontal symmetry allows for new solutions to the solar and atmospheric neutrino problems that do not involve modification of the original charged fermion Yukawa textures, or the introduction of sterile neutrinos. (C) 2000 Elsevier Science B.V.
Keywords: atomic particle; energy; mathematical model; physics